2021
DOI: 10.3390/v13112182
|View full text |Cite
|
Sign up to set email alerts
|

The Evolutionary Landscape of SARS-CoV-2 Variant B.1.1.519 and Its Clinical Impact in Mexico City

Abstract: The SARS-CoV-2 pandemic is one of the most concerning health problems around the globe. We reported the emergence of SARS-CoV-2 variant B.1.1.519 in Mexico City. We reported the effective reproduction number (Rt) of B.1.1.519 and presented evidence of its geographical origin based on phylogenetic analysis. We also studied its evolution via haplotype analysis and identified the most recurrent haplotypes. Finally, we studied the clinical impact of B.1.1.519. The B.1.1.519 variant was predominant between November… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
40
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 62 publications
7
40
1
Order By: Relevance
“…Never before had a VOC displaced other variants so quickly in Mexico City. In 2021, variant B.1.1.519 was totally displaced by Alpha, Gamma, and Delta in four months [ 6 ], while the Omicron variant displaced Delta in only one month. There was a correlation between the growth of the epidemic curve and the proportion of Omicron variants ( Figure 2 C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Never before had a VOC displaced other variants so quickly in Mexico City. In 2021, variant B.1.1.519 was totally displaced by Alpha, Gamma, and Delta in four months [ 6 ], while the Omicron variant displaced Delta in only one month. There was a correlation between the growth of the epidemic curve and the proportion of Omicron variants ( Figure 2 C).…”
Section: Resultsmentioning
confidence: 99%
“…Mexico City has been heavily affected by the COVID-19 pandemic. Two intense epidemic waves occurred in spring 2020 and winter 2020/2021, during which the heaviest toll of hospitalizations and deaths was observed [ 5 , 6 ]. A vaccination campaign began, starting with frontline health care workers and continuing for the rest of the population in descending age order, and was completed in the fall of 2021.…”
Section: Introductionmentioning
confidence: 99%
“…Never before had a variant of concern (VOC) displaced other variants so quickly in Mexico City, in 2021 variant B.1.1.519 was totally displaced by Alfa, Gamma and Delta in four months [5], while the Omicron variant displaced Delta in only one month. There was a correlation between the growth of the epidemic curve and the proportion of Omicron (Figure 2C).…”
Section: Identification Of Omicron Variant In Mexico Citymentioning
confidence: 99%
“…Mexico City has been heavily affected by the COVID-19 pandemic. Two intense epidemic waves occurred in spring 2020 and winter 2020/2021, during which the heaviest toll of hospitalizations and deaths was observed [4,5]. A vaccination campaign began, starting with frontline healthcare workers and continuing in descending age order, and was completed in fall 2021 (http://vacunacovid.gob.mx/wordpress/calendario-vacunacion/).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, research findings revealed unique amino acid substitutions by characterizing the mutational patterns and the effect on the corresponding proteins. Cedro-Tanda et al [7] reported the emergence and spread of the new B.1.1.519 variant in Mexico City in the beginning of 2021, and described its evolution, transmissibility, and association with relevant clinical traits. The authors observed that variant B.1.1.519 was significantly associated with severe disease, hospitalization, and death.…”
mentioning
confidence: 99%